Het oostelijk ringspoor van Brussel: groeibarrière in de 19e en 20e eeuw? (1855-1950) - Alix Sacré (Brussels Studies)
How did the development of the railways affect the urban morphology of the Brussels suburbs? In an attempt to provide a first answer to this broad question, this article examines the role of railway infrastructures of the east railway ring in Brussels (currently line 161). Above all, it proposes to demonstrate that, contrary to a preconceived and still widespread idea, the tremendous development of the rail network in the second half of the 19th century was sometimes a huge obstacle to the urbanisation of certain neighbourhoods, with what could be referred to as “growth barriers” being built in the middle of them. By comparing archives of different types - in particular cartographic (mainly from municipal archives) - and various works on the evolution of urban morphology, through the example of this ring line, this study shows that while stations have often promoted urban development as economic growth areas, the railways crossing the city have had the opposite impact, sometimes acting as obstacles to the growth of certain neighbourhoods.